Horse Trading in the Age of Cars Men in the Marketplace - Gelber, Steven M. (Johns Hopkins University Press, 2008)
The trading, selling, and buying of personal transport has changed little over the past one hundred years. Whether horse trading in the early twentieth century or car buying today, haggling over prices has been the common practice of buyers and sellers alike. Horse Trading in the Age of Cars offers a fascinating study of the process of buying an automobile in a historical and gendered context. Steven M. Gelber convincingly demonstrates that the combative and frequently dishonest culture of the showroom floor is a historical artifact whose origins lie in the history of horse trading. Bartering and bargaining were the norm in this predominantly male transaction, with both buyers and sellers staking their reputations and pride on their ability to negotiate the better deal. Gelber comments on this point-of-sale behavior and what it reveals about American men. Gelber's highly readable and lively prose makes clear how this unique economic ritual survived into the industrial twentieth century, in the process adding a colorful and interesting chapter to the history of the automobile.